EFEKTIVITAS STRATEGI COPING DENGAN RESILIENSI PTSD BAGI ANAK DAN REMAJA PENYINTAS BENCANA ALAM - Carmenita, Mutiara Anastasia; Budianto, Raymond Elbert; Sudastra, Ni Putu Dinda Pramesti (Essence of Scientific Medical Journal; Vol 22 No 1 (2024): Volume 22 No. 1 (Januari - Juni 2024) Essential: Essence of Scientific Medical Journal, 2024)
Introduction: The "Ring of Fire" moniker for Indonesia signifies that natural disasters are an inescapable part of our daily lives. These disasters not only cause material losses but also can inflict deep psychological trauma on those who experience them. One common psychological condition that can arise is PTSD (Post Traumatic Stress Disorder). Discussion: Children and teenagers are particularly vulnerable to PTSD due to their still-developing physical and intellectual capacities. Various psychological interventions can help address this condition, one of which is coping strategies. The purpose of this writing is to determine the effectiveness of coping strategies in enhancing resilience against PTSD for child and adolescent survivors of natural disasters. A literature review was conducted on 19 articles and journals sourced from Google Scholar and Pubmed. The results of the literature review indicate that coping strategies influence the occurrence of PTSD in children and adolescents who have lost family members following natural disasters. Conclusion: Emotion-focused coping strategies are considered more effective than problem-focused coping strategies because the source of the problem stems from an unchangeable situation. Some effective emotion-focused coping strategies include seeking social support through community and professional consultations, channeling burdens through activities, and fostering a closer relationship with God.